Modeling of the effective functioning of the agricultural lands market in Ukraine - Stupen, Roman; Stupen, Mykhailo; Ryzhok, Zoriana; Stupen, Oksana (Geodesy and Cartography, 2019)
The article deals with the main problems of creating the agricultural lands market in Ukraine due to the absence of the normative and legal support of its circulation, which should define the set of rights and restrictions of the implementation of this process. It is determined that the agricultural lands market is a social and economic complex that functions in accordance with market laws, national specificity, territorial scope and consists of a set of enterprises, establishments and representative offices, which are directly related to turnover of agricultural lands market. The main prerequisites for formation of effective functioning of the agricultural lands market are substantiated. Structural and logical scheme of this process implementation is constructed. Despite the ban on the purchase and sale of agricultural lands, the market value of land for private peasant farming has been calculated according to an expert assessment of a comparative methodological approach in determining the degree of similarity of objects using the Euclidean distance. The proposed method is appropriate to use in determining the market land value, regardless of its target use, by the degree of similarity of the objects of comparison according to the area, location, physical characteristics, functional characteristics and the availability of improvements, which allows to take into account its quantitative and qualitative characteristics.